Perencanaan Green Infrastructure pada Kawasan Transit Oriented Development (TOD) Lebak Bulus, Jakarta Selatan - Hakim, Annisa Laini; Sulistyantara, Bambang (http://arl-faperta.ipb.ac.id/, 2024)
Transit Oriented Development (TOD) approach is one of the solutions adapted by DKI Jakarta’s Government in order to create a walkable and mass transportation friendly environment in Jakarta. Lebak Bulus TOD in its development will use environmental sustainability approach in order to reduce negative impact from urban development. However, Lebak Bulus TOD is currently lacked of green open space and dominated with impermeable surface that affect the increase of the stormwater runoff. Implementing green infrastructure concept in planning Lebak Bulus TOD site is one of the solution to overcome the problems. This research is aimed to reduce stormwater runoff and pollution in Pasar Jumat Street, Lebak Bulus Raya Street, and RA Kartini Street located in Lebak Bulus TOD. The methods used in this research are descriptive, quantitative analysis, and spatial analysis. Quantitative analysis is used to calculate water quality volume for each location, the results for each location respectively are 832,56 m3, 205,44 m3, dan 205,7 m3. Green infrastructure system used are stormwater tree trench, stormwater planter, green gutter, permeable pavement, and green wall. 285,95 m3 of stormwater runoff can be reduced by the implementation of green infrastructure. Spatial analysis using CITYGreen shows that the planning can reduce pollution by 48,83 kg/year with economic value of 263,49 (Rp3.751.834,11) and reduce runoff volume by 51% with economic value of 2.408,67 (Rp34.348.838).